Problems of Usage Labelling in English Lexicography - Sakwa, Lydia Namatende (Lexikos, 2011)
Landau (1991: 217) stipulates that ’usage refers to any or all uses of language’. It is the study of good, correct, or standard uses of language as distinguished from bad, incorrect, and nonstandard uses of language. Usage may also include the study of any limitations on the method of use, whether geographic, social or temporal. Basically it alerts users that certain terms should not be uncritically employed in communication. This article discusses the treatment of usage in English lexicography. It analyses the labelling practices in six monolingual English dictionaries namely: the Oxford Advanced Learner’s Dictionary (OALD), the Macmillan English Dictionary (MED), the Longman Dictionary of Contemporary English (LDOCE), the Cambridge International Dictionary of English (CIDE), the World Book Dictionary (WBD) and the New Shorter Oxford English Dictionary (NSOED). Discrepancies in the contextual usage labelling in the dictionaries were established and are discussed.